The production of microbial biodiesel from cellulose-derived fungal lipid via consolidated bioprocessing - Hasni, Mohd Haffizi; Ahmad, Farah; Athoillah, Ahdyat Zain (Elsevier, 2023)
Lignocellulosic biomass from agro-industrial residues can potentially be used as carbon-rich carbohydrate feedstock for the conversion via oleaginous microorganisms into lipids, and subsequently microbial biodiesel. As multiple processes are required to conventionally convert lignocellulosic biomass into lipids, from the hydrolysis of carbohydrate into simple sugars for the fermentation, it is not economically favourable. Consolidated bioprocessing (CBP) combines the saccharification and fermentation of lignocellulosic biomass into a single processing step. As such, this study aims to screen multiple oleaginous fungi to identify the most effective lipid producers in CBP systems, followed by optimization study. Three different fungi (Aspergillus niger, Aspergillus oryzae, and Rhizopus sp.) were screened by the co-cultivation of monosaccharides. Rhizopus sp. yielded the highest lipid content. The response surface methodology (RSM) was used to optimize​ lipid production by Rhizopus sp. from cellulose in CBP systems. The CBP system with carbon concentration of 0.8% (w/v), temperature of 32 °C, and carbon to nitrogen ratio (C/N) of 99.5, yielded the optimum lipid content (51.8%). The lipid from Rhizopus sp. was then converted into biodiesel, that comprised 56.0% of saturated fatty acids. Fuel properties analysis indicated that microbial biodiesel from lipids of Rhizopus sp. is a promising alternative to diesel fuel.